Elevated Hb A2 levels in a patient with a compound heterozygosity for the (β +)-31 (A > G) and (β 0) Codon 17 (A > T) mutations together with a single α-globin gene - Sitthichai Panyasai (2018)
© 2015 Informa Healthcare USA, Inc. We report the molecular and hematological feature of a Thai woman who had clinical diagnosis of β-thalassemia intermedia (β-TI). Hemoglobin (Hb) high performance liquid chromatography (HPLC) analysis identified Hb A (64.4%), Hb F (12.3%) and Hb A < inf > 2 < /inf > /E (15.9%) with small peaks of Hb Barts (γ4) and Hb H (β4). She was initially diagnosed as EA Barts disease, which occurs from combination of Hb H disease and Hb E (HBB: c.79G > A) trait. However, the Hb analysis using capillary electrophoresis (CE) demonstrated no Hb E, 68.5% Hb A, 15.5% Hb F and 16.0% Hb A < inf > 2 < /inf > . DNA analysis showed a compound heterozygosity for (β < sup > + < /sup > )-31 (A > G) (HBB: c.-81A > G) and (β < sup > 0 < /sup > ) codon 17 (A > T) (HBB: c.52A > T) mutations and deletional Hb H (- < sup > SEA < /sup > /-α < sup > 3.7 < /sup > ). Thus, she was finally diagnosed with a combination of Hb H disease and compound heterozygosity of β < sup > + < /sup > /β < sup > 0 < /sup > -thalassemia (β < sup > + < /sup > /β < sup > 0 < /sup > -thal). The β-globin mutations could affect not only hematological parameters but also elevate the Hb A < inf > 2 < /inf > levels. These effects could not be ameliorated by the coinheritance of Hb H disease. Therefore, a better understanding of the effects of this combination on hematological analysis data will be useful for providing accurate diagnosis, genetic counseling, prevention and control programs of β-thalassemia major (β-TM).